2018
DOI: 10.5897/ajmr2017.8743
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antibiotic resistance patterns of Pseudomonas spp. isolated from clinical samples of a hospital in Madinah, Saudi Arabia

Abstract: Pseudomonas spp. are the leading cause of nosocomial infections. Rise in multidrug resistance among clinical isolates limit therapeutic options and hence increase mortality rate. Clinical samples (6840) from a hospital in Madinah, Saudi Arabia were collected for a duration of 14 months to study the frequency, antimicrobial sensitivity pattern and seasonal variations of Pseudomonas isolates. Conventional biochemical tests were done to identify the probable organism and antibiotic susceptibility was performed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…In our study maximum resistance was noted to amoxicillin+clavulinic acid 74.3% which is similar to that reported by Igbalajobi et al, 76.2%, 12 where as Walaa M. Saeed et al, reported much lower resistance to the drug 25%. 20 Next resistant drug in our study was ciprofloxacin 40.1% which is similar to the study conducted by Nishi Tiwari et al, 43%. 11 33.0% of Pseudomonas aeruginosa isolates in our study were resistant to amikacin which is similar to the studies conducted by Nishi Tiwari et al, 41%, 11 whereas Saroj Golia et al, reported only 13.3% of resistance to amikacin much lower than our study.…”
Section: Characterization Of Bacterial Isolatessupporting
confidence: 90%
“…In our study maximum resistance was noted to amoxicillin+clavulinic acid 74.3% which is similar to that reported by Igbalajobi et al, 76.2%, 12 where as Walaa M. Saeed et al, reported much lower resistance to the drug 25%. 20 Next resistant drug in our study was ciprofloxacin 40.1% which is similar to the study conducted by Nishi Tiwari et al, 43%. 11 33.0% of Pseudomonas aeruginosa isolates in our study were resistant to amikacin which is similar to the studies conducted by Nishi Tiwari et al, 41%, 11 whereas Saroj Golia et al, reported only 13.3% of resistance to amikacin much lower than our study.…”
Section: Characterization Of Bacterial Isolatessupporting
confidence: 90%